Damage Currency Swap the Resulting From Government Departments Dealing With Trade Bank of Iraq From - حسب الله, احمد سامي; شلاكة, جواد كاظم (Journal of Economics and Administrative Sciences, 2013)
Interested current Research measuring damage currency Swap by converting The ministry of higher Education and scientific Research money The Iraqi dinar To U.S dollar by Trade Bank Of Iraq , And that The damage Generated resulting from Deferent Between the Exchange Rate adopted From Central Bank of Iraq and Market Exchange Rate adopted by The Trade Bank Of Iraq , and Which led to the greet damage ( losses ) in Bearing by the ministry, which led to the reduction of the financial allocations for licensed curriculum outside of Iraq , and this in turn leads  to reduction in the number of students Sender ( scholarships )  outside Iraq.Where the estimated loss (damage) that suffer by the Ministry of Higher Education and Scientific Research for the year 2006 to 2011 amounted to ($ 4,593,314) and the estimated loss for the year 2012 amount ($ 8,793,871) and because of the high exchange rate calculated by the Trade Bank of Iraq compared to the exchange rate announced by the Central Bank of Iraq, and thus the Ministry of Higher Education and Scientific Research has incurred losses estimated at (13,387,185 $) (thirteen million and three hundred and eighty-seven thousand and one hundred and eighty-five dollars) for the period from the year 2006 until the year 2012, equivalent to (15,794,549,743 dinars) (fifteen billion and seven hundred and Ninety-four million and five hundred and forty-nine thousand and seven hundred and forty-three dinars) and this will lead to a reduction of allocations of the Ministry of account certified curriculum, which reflected negatively on the performance of the ministry, and thus lead to a reduction in the number of students abroad, due to the high exchange rate calculated by the Trade Bank of Iraq compared to the exchange rate announced by the Central Bank of Iraq and a very large margin.